Concentration-effect relationships for intravenous alfentanil and ketamine infusions in human volunteers: effects on acute thresholds and capsaicin-evoked hyperpathia - Wallace, Mark S; Ridgeway, 3rd, Beri; Leung, Albert; Schulteis, Gery; Yaksh, Tony L (Journal of clinical pharmacology, 2002)
The authors have extended preclinical studies on pain to human volunteers by examining the effects of intravenous alfentanil and ketamine on acute sensory thresholds andfacilitated processing induced by intradermal capsaicin. Eleven healthy subjects received targeted plasma concentrations of alfentanil, ketamine, and placebo followed by neurosensory testing (thermal and von Frey hair thresholds). After completing the tests at the highest plasma level, intradermal capsaicin was injected into the volar aspect of the left forearm, and the flare response and hyperalgesia to von Frey hair, stroking, and heat were assessed. Alfentanil significantly elevated cool and warm thresholds and decreased capsaicin-induced stroking hyperalgesia. Ketamine significantly decreased capsaicin-induced von Frey hair hyperalgesia. Both drugs resulted in a significant elevation of von Frey hair-induced pain thresholds and a decrease in capsaicin-induced pain. These studies suggest that experimental human pain models may be used to study analgesic pharmacology and may serve as important methods for defining the analgesic efficacy of drugs in phase I clinical trials.